Post-transcriptional regulation of mouse neurogenesis by Pumilio proteins - Zhang, Meng; Chen, Dong; Xia, Jing; Han, Wenqi; Cui, Xiekui; Neuenkirchen, Nils; Hermes, Gretchen; Sestan, Nenad; Lin, Haifan (Genes & development, 2017)
Despite extensive studies on mammalian neurogenesis, its post-transcriptional regulation remains under-explored. Here we report that neural-specific inactivation of two murine post-transcriptional regulators, Pumilio 1 (Pum1) and Pum2, severely reduced the number of neural stem cells (NSCs) in the postnatal dentate gyrus (DG), drastically increased perinatal apoptosis, altered DG cell composition, and impaired learning and memory. Consistently, the mutant DG neurospheres generated fewer NSCs with defects in proliferation, survival, and differentiation, supporting a major role of Pum1 and Pum2 in hippocampal neurogenesis and function. Cross-linking immunoprecipitation revealed that Pum1 and Pum2 bind to thousands of mRNAs, with at least 694 common targets in multiple neurogenic pathways. Depleting Pum1 and/or Pum2 did not change the abundance of most target mRNAs but up-regulated their proteins, indicating that Pum1 and Pum2 regulate the translation of their target mRNAs. Moreover, Pum1 and Pum2 display RNA-dependent interaction with fragile X mental retardation protein (FMRP) and bind to one another's mRNA. This indicates that Pum proteins might form collaborative networks with FMRP and possibly other post-transcriptional regulators to regulate neurogenesis.